Cognitive processing in a multimedia lesson: An action research study in a language classroom - Monika, Yunias (Institut Agama Islam Negeri Kendari, 2026)
This study examines how multimedia-based instruction supports learners’ cognitive processing in an English for Academic Purposes (EAP) classroom, addressing the limited understanding of cognitive demands in multimedia learning materials. Employing classroom-based action research, the study involved 59 undergraduate students enrolled in an EAP course at a private university in Indonesia. Data were collected through group mind maps, students’ self-reported mental effort using Paas’ 9-point scale, and course evaluation surveys. The analysis combined qualitative content analysis guided by the Cognitive Theory of Multimedia Learning (CTML) with descriptive analysis of mental effort ratings. The findings suggest that multimedia instruction may facilitate meaningful learning and improve students’ engagement with academic content. Nevertheless, learners demonstrated varying levels of cognitive processing, with some experiencing difficulties integrating multimodal information and reporting higher cognitive load.